Comparison and Verification of Stress Measurement Results Using the Barkhausen Effect during Three-Point Bending - Domański, Tomasz; Piekarska, Wiesława; Saga, Milan; Saternus, Zbigniew; Kubiak, Marcin; Vasko, Milan (Manufacturing Technology Journal, 2025)
Non-destructive stress measurement techniques are extremely important and are still being developed in engineering research and diagnostics of materials. They allow for a quick assessment of their condition without damaging the structure. Their development is crucial for the safety of structures and extending the life of materials. One of the new methods is the measurement of stress using the Barkhausen effect. The MagStress 5d device was used for the tests. In this work, stress measurements were performed using the MagStress 5D device during three-point bending of a steel flat bar. The results were verified using resistance strain gauges and numerical simulation was performed in the Abaqus program. The measurements indicate that the MagStress 5d device using the Barkhausen effect can serve as a complete alternative to traditional extensometers. The results provided by the introduced method showed very good agreement with the latter.
Keywords: Bending testing; Numerical modelling; Barkhausen effect; Stress - strain analysis; S355 steel